West African 'ulamā' and Salafism in Mecca and Medina : jawab al-Ifrīqī-the response of the African - Ahmed, Chanfi. (Islam in Africa, 2015)
Chanfi Ahmed shows how West African ʿulamāʾ, who fled the European colonization of their region to settle in Mecca and Medina, helped the regime of King Ibn Sa'ud at its beginnings in the field of teaching and spreading the Salafῑ-Wahhabῑ's Islam both inside and outside Saudi Arabia. This is against the widespread idea of considering the spread of the Salafῑ-Wahhābῑ doctrine as being the work of ʿulamāʾ from Najd (Central Arabia) only. We learn here that the diffusion of this doctrine after 1926 was much more the work of ʿulamāʾ from other parts of the Muslim World who had already acquired this doctrine and spread it in their countries by teaching and publishing books related to it. In addition Chanfi Ahmed demonstrates that concerning Islamic reform and mission (daʿwa), Africans are not just consumers, but also thinkers and designers.